(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
Six principal areas of research seemed to present themselves. The nature of the sites themselves, their structures and deposits constitute the first and their chronology, the second. The regional environment in which they functioned, through time, may be considered next, because it sets outer limits to the possibilities for the development of the economies of the sites, the fourth research area. Technology and trade, while aspects of site economy, merit separate consideration and the settlement landscape, the distribution and location of these sites is also of sufficient importance to stand alone, as a research topic. A list of questions for the sites is listed under the following subheadings: the sites; deposits; structures; artefacts; chronology; regional environment; site economies; technology; trade; site distribution and location. This is followed by the methods employed to answer them. Specialist methodologies comprise those for coarse pottery, mammalian fauna, fish bones, pollen, charred plant remains, snails, phytoliths, lake sediments and diatoms.